How Should Fiscal Policy Be Set Over the Business Cycle? - Talvi, Ernesto (World Bank, Washington, DC, 2012)
Several generations of economists have analyzed the relationship between fiscal policy and the business cycle. How is fiscal policy actually conducted over the business cycle? From a public policy point of view, the interpretation based on credit market imperfections calls for ensuring that developing countries retain access to international credit markets in bad times. At the domestic level, effective liquidity management and intertemporal solvency of fiscal accounts have been emphasized for countries to avoid being cut off from international credit markets in bad times.